Dandy-Walker malformasyonunda endoskopik III. ventrikülostominin rolü - (:unkn) unknown (My University, 2004)
Günümüzde endoskopik III. ventrikülostomi, non-kommünike hidrosefalide ilk tedavi seçeneği olarak kabul edilmektedir. Hekimlerin hastalarına şanttan bağımsız bir hayat sunabilme arzusu, bu tekniğin diğer hasta gruplarında da uygulanmaya başlamasını sağlamıştır. Bu çalışmada amaç, endoskopik III. ventrikülostomi uygulanan 9 Dandy-Walker malformasyonlu hastayı geriye dönük olarak gözden geçirerek, başarı ve komplikasyon oranlarını sunmaktır. Hastaların 5'i erkek, 4'ü kızdı. Yaş ortalaması 13 aydı. Endoskopik III. ventrikülostomi sonrası şant gerektirmeyen tüm olgular başarılı olarak kabul edildi. Ortalama takip süresi 25 aydı. Hastaların %78'inde başarı sağlandı. Bir olguda geçici 3. sinir parezisi gözlendi. Sonuç olarak endoskopik III. ventrikülostomi, Dandy-Walker tanısı olan hastalara, şanttan bağımsız bir hayat sürme şansını sunabilir.

Currently, endoscopic third ventriculostomy is considered as the first choice in the treatment of non-communicating hydrocephalus. But the urge of the physician, to provide a shunt-free survival for his patients, leads to performing the procedure in a diverse group of patients. The aim of this study was to review 9 cases of endoscopic third ventriculostomy -performed in patients with Dandy-Walker malformation- retrospectively, to report the rates of success and complications. Five of the patients were male and 4 were female. The average age of the patients was 13 months. All the cases, who did not required a shunt surgery following endoscopic third ventriculostomy, was considered as successful!. Average follow-up period was 25 months. The rate of success was 78%. A transient $3^{rd}$ nerve paresis was observed in one of the patients. As a conclusion, endoscopic third ventriculostomy can provide a shunt-free survival for the patients with Dandy-Walker malformation.
The role of endoscopyic third ventriculostomy in Dandy-Walker malformation
Keywords: Genel ve Dahili Tıp